Stopping the Resuscitation When Family Is Present: Teaching Ethical and Professional Challenges. Issue 3 (June 2017) - Shamis, Justin; Hawryluck, Laura; Christian, Michael D.; Devine, Luke
Abstract : Supplemental digital content is available in the text.